Phytophagous insects and predatory arthropods in soybean and zinnia - Erise Anggraini; wida nur anisa; siti herlinda; Chandra Irsan; suparman SUPARMAN; suwandi suwandi; muhammad umar harun; BAMBANG GUNAWAN (Society for Indonesian Biodiversity, 2021)
Abstract. Anggraini E, Anisa WN, Herlinda S, Irsan C, Suparman S, Suwandi S, Harun MU, Gunawan B. 2021. Phytophagous insects and predatory arthropods in soybean and zinnia. Biodiversitas 22: 1405-1414. In Indonesia, soybean is the third most important commodity after rice and corn. Cultivation technique such as planting hedgerows was expected to attract and retain natural enemies of pest predators. This study was conducted to determine the phytophagous insects and predatory arthropods species in soybean (Glycine max L.) and zinnia (Zinnia sp., hybrids) plants as refugia. This study utilized three methods i.e., visual observation, pitfall trap, net-trap in both soybean and zinnia planting areas. All collected insects were carried to the laboratory for observation and identification using insect determination key book. Insect identification was based on their morphological characteristics. The results study showed that phytophagous and predatory arthropods were found in both soybean and zinnia plantations in Agro-Techno Center (ATC), Sriwijaya University, Indonesia. There were 11 species of phytophagous and 5 species of entomophagous insects identified at soybean cultivation. Meanwhile, 5 species of phytophagous and 9 species of predatory arthropods including five spider species found, namely Pardosa distincta, Oxyopes javanus, Lycosa pseudomonas, Pardosa sp. and Drapetisca socialis at zinnia cultivation area. However, chi-square analysis (at alpha 0.05), confirmed that there was no significant difference between predatory arthropods in soybean and Zinnia the results indicate that soybean is might be suitable to be planted as refugia for predatory arthropods.